1995
DOI: 10.1126/science.7604282
|View full text |Cite
|
Sign up to set email alerts
|

The TBP-TFIIA Interaction in the Response to Acidic Activators in Vivo

Abstract: A yeast TBP mutant (N2-1) is described here that is defective specifically in responding to acidic activators in vivo. N2-1 does not support activation by Gal4, Ace1, and Gcn4, but appears unaffected for constitutive transcription, repression by the Cyc8-Tup1 and Not complexes, and transcription by polymerase I (Pol) and Pol III. In vitro, N2-1 fails to interact with TFIIA, but it associates normally with a TATA element, an acidic activation domain, and TFIIB. Fusion of the small subunit of TFIIA to N2-1 resto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 46 publications
8
114
2
Order By: Relevance
“…(iv) Mutations affecting the surface of TBP that interacts with TFIIA reduce TFIIA binding in vitro and also interfere with transcriptional activation in vivo (6,41). (v) As reported here, a correlation exists between DA-complex assembly activity and in vivo activation function for mutants of VP16C.…”
Section: (Iii) Formentioning
confidence: 78%
See 1 more Smart Citation
“…(iv) Mutations affecting the surface of TBP that interacts with TFIIA reduce TFIIA binding in vitro and also interfere with transcriptional activation in vivo (6,41). (v) As reported here, a correlation exists between DA-complex assembly activity and in vivo activation function for mutants of VP16C.…”
Section: (Iii) Formentioning
confidence: 78%
“…These results suggest that TFIIB binding is not a limiting step in transcription, as might be expected for a regulated step. In contrast, mutations in TBP residues in the interface between TBP and TFIIA that reduce the affinity of TFIIA for the TBP-TATA box complex severely reduce the ability of TBP to participate in activated transcription in vivo but do not impair basal transcription (6,41).…”
Section: (Iii) Formentioning
confidence: 99%
“…The high local concentration afforded by this tether and its flexibility should diminish the sensitivity of Brf1c⅐Bdp1 binding to adventitious effects of mutations on Brf1c⅐TBPc binding. A similar approach was used to rescue the TFIIA binding defect of a TBP mutant protein in yeast (18). The ability of TBPc-Brf1c to assemble Bdp1 onto DNA and to function for transcription has been documented (8) and is further analyzed below.…”
Section: Resultsmentioning
confidence: 99%
“…Results of crystallographic and mutant analyses of TBP revealed that Ala-184/Leu-185 (86/87), Asn-189 (91), and Arg-205 (107) in the ␣-helix 1, ␤-sheet 2, and COOH terminus adjacent to the ␤-sheet 3 region of the tandem repeat of human TBP (yeast TBP) made contact with amino acids of TOA2 and were required for TFIIA binding (6,52,53). Basic amino acids in the ␣-helix 2 region have been proposed to be involved in TBP-DNA-TFIIA complex formation (55,56). Mutation of basic amino acids at Arg-231 and Arg-239 in this region of human TBP diminished the binding ability to the TFIIA column (6).…”
Section: Discussionmentioning
confidence: 99%